A unique delaminated MoS4/OS-LEuH composite exhibiting turn-on luminescence sensing for detection of water in formamide. Issue 10 (7th February 2017) - Xie, Linxia; Liu, Chenyu; Ma, Lijiao; Xiao, Chengliang; Ma, Shulan; Sun, Genban; Li, Huifeng; Yang, Xiaojing
Abstract : A delaminated MoS4 /OS-LEuH composite showed quenched luminescence in pure formamide while highly enhanced emission in the water-present case. Abstract : We demonstrate a novel example of a delaminated MoS4 /OS-LEuH composite (LEuH is layered europium hydroxide, OS is 1-octane sulfonate), which exhibits quenched luminescence in formamide and highly enhanced red emission in the water-present case. The turn-on luminescence sensing capability of the material is promising for feasible detection of a trace amount of water in formamide (FM) and N, N -dimethylformamide (DMF).